2020
DOI: 10.1126/sciadv.abc1725
|View full text |Cite
|
Sign up to set email alerts
|

Trisulfide bond–mediated doxorubicin dimeric prodrug nanoassemblies with high drug loading, high self-assembly stability, and high tumor selectivity

Abstract: Rational design of nanoparticulate drug delivery systems (nano-DDS) for efficient cancer therapy is still a challenge, restricted by poor drug loading, poor stability, and poor tumor selectivity. Here, we report that simple insertion of a trisulfide bond can turn doxorubicin homodimeric prodrugs into self-assembled nanoparticles with three benefits: high drug loading (67.24%, w/w), high self-assembly stability, and high tumor selectivity. Compared with disulfide and thioether bonds, the trisulfide bond effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(128 citation statements)
references
References 40 publications
3
124
0
1
Order By: Relevance
“…For instance, compared with disulfide and thioether linkers, the trisulfide bond effectively promotes the self-assembly ability of DOX homodimeric prodrugs (Figure 5D), thereby improving the colloidal stability and the fate of prodrug nanoassemblies; further MD simulation disclosed that the trisulfide bond had more sulfur-containing bond angles, and were close to 90°, [80] which were believed the optimal angle to constructed the most stable conformation, and kept agreement with the lowest calculated free energy. [80] Amino acid valine linked PTX and MTX to offered prodrug conjugate then assembled into NPs. [81] It is also found that the drug-drug conjugate may change the mechanism of action, exemplified by temozolomide (TMZ)-Dox prodrug double intercalating with DNA although TMZ itself is a weak DNA binder and functioned as an induced intercalator.…”
Section: Chemical Reaction Obtained Drug-drug Conjugate Prodnmsmentioning
confidence: 70%
“…For instance, compared with disulfide and thioether linkers, the trisulfide bond effectively promotes the self-assembly ability of DOX homodimeric prodrugs (Figure 5D), thereby improving the colloidal stability and the fate of prodrug nanoassemblies; further MD simulation disclosed that the trisulfide bond had more sulfur-containing bond angles, and were close to 90°, [80] which were believed the optimal angle to constructed the most stable conformation, and kept agreement with the lowest calculated free energy. [80] Amino acid valine linked PTX and MTX to offered prodrug conjugate then assembled into NPs. [81] It is also found that the drug-drug conjugate may change the mechanism of action, exemplified by temozolomide (TMZ)-Dox prodrug double intercalating with DNA although TMZ itself is a weak DNA binder and functioned as an induced intercalator.…”
Section: Chemical Reaction Obtained Drug-drug Conjugate Prodnmsmentioning
confidence: 70%
“…These results confirmed the good colloidal stability of four NPs. The stability of iRGD-TK-NP and TK-NPs was higher than that of iRGD-CC-NPs as well as CC-NPs, which may be due to the fact that the TK linkage improves the structural flexibility of dimeric prodrugs, thereby increasing the stability of DPNS (Yang et al, 2020). NPs 91.8 ± 2.1 0.21 ± 0.03 -(17.7 ± 0.7) 50.1 ± 2.1 75.3 ± 2…”
Section: Characterization Of Tk-npsmentioning
confidence: 92%
“…The stability of iRGD-TK-NP and TK-NPs was higher than that of iRGD-CC-NPs, which may be due to the fact that the TK linkage improves the structural exibility of dimeric prodrugs, thereby increasing the stability of DPNS. [34] When the addition of H 2 O 2 , UA release behavior was enhanced and sustained. In the presence of 1 mM H 2 O 2 , around 25% of UA was released from NPs after 48 h incubation.…”
Section: Characterization Of Tk-npsmentioning
confidence: 98%